Inulin, KCL, and Flavor Enhancers: An Efficient Combination to Produce Prebiotic and Low-Sodium Burgers - dos Santos, Bibiana Alves; Cichoski, Alexandre José; Campagnol, Paulo Cezar Bastianello (Frontiers in Animal Science, 2021)
In this study, prebiotic and low-sodium burgers were produced. In the first experiment, burgers were elaborated with 0, 3, 6, 9 and 12% inulin. The addition of up to 9% inulin did not affect the sensory quality, increased yield and reduced shrinkage. Thus, in the second experiment, prebiotic burgers were produced with 9% inulin and a sodium reformulation was performed by replacing 60% NaCl with KCl and adding monosodium glutamate (MG) and / or liquid smoke (LS). The replacement of NaCl for KCl impaired the sensory quality of the burgers. The isolated or combined addition of MG and LS reduced the sensory defects caused by KCl. Thus, prebiotic and low-sodium burgers with high technological and sensory quality can be produced using 9% inulin, 1% NaCl, 1.5% KCl, 0.2% MG and 0.1% LS.